Highly Nondegenerate Four-Wave Mixing in Single-Mode Fabry-Pérot Laser Diode Subject to Dual-Mode Injection - Jian-Wei Wu; Nakarmi, Bikash; Yong Hyub Won (IEEE photonics journal, 2016)
In this paper, highly nondegenerate four-wave mixing (NDFWM) resulting from external dual-mode injection (pump-probe structure) in the single-mode Fabry-Pérot laser diode (SMFP-LD) is proposed and experimentally demonstrated. To cause the effective NDFWM process, both pump and probe beams with enough power levels should, respectively, be close to various resonance modes in the active region, whose detuning frequency can be discontinuously varied from more than 100 GHz to up to 800 GHz. Normalized conversion efficiency (NCE) and optical signal-to-noise ratio (OSNR) of newly generated conjugate signals are strongly dependent on external injection power, wavelength detuning, and detuning frequency. In addition, the NDFWM process exhibits injection probe power-related hysteresis behaviors, whereas the input power and wavelength for pump beam are, respectively, fixed at some special constants.